Jihad Digital: Pembingkaian Narasi Kontra Radikalisasi NU Online di Dunia Maya - Sefriyono, Sefriyono (FIKRAH, 2020)
The development of digitalization has shifted the institutionalization values patterns from conventional to cyberspace, it is containing radical values through the website which also developed along with the development of digitalization. Radicalization in cyberspace requires the counter-sites which committed to religious moderation. NU Online is one of this counter-site. This study uses qualitative methods with data analysis framing techniques. NU Online distinguishes the radicalization and intolerance narratives in cyberspace is a source of the uproar of the national ideology and disharmony in the interfaith relations. In its prognosis strategy, NU Online develops the narratives such as Islam is very compatible with Pancasila. While in its motivational strategy, NU Online invites all elements of the nation to maintain the integration of the nation by publishing the headline such as “four reasons for rejecting the Khilafah”. This counter-radicalization framing is different from that carried out by panjimas.com as a representation of the radical site